In the shadow of melting glaciers climate change and Andean society - Carey, Mark (Mark P.) (Oxford University Press, 2010)
Illustrating in detail how people in the Andes have grappled with the effects of climate change and ensuing natural disasters for more than half a century, this book's historical perspective illuminates the trends that would be ignored in scientific projections about future climate scenarios.